Forced Labor and Health-Related Outcomes. The Case of Beggar Children - Nick Drydakis (Institute of Labor Economics (IZA), 2023)
The study aims to examine whether beggar children are victims of forced labor, as well as to identify the manifestations of forced labor in beggar children, and assess whether forced child begging relates to deteriorated health-related quality of life and mental health. The study focused on the capital city of Greece, Athens, where beggar children are not a hard-to-reach group. Cross-sectional data were collected in 2011, 2014, 2018 and 2022, with 127 beggar children taking part in the study. The study adopted the Anti-Slavery International research toolkit, which sets methodological guidelines on researching child begging. A scale was developed to quantify forced child begging based on the International Labour Organization's definition of forced labor. The study found that most beggar children were forced by others to beg, experienced threats of violence, physical and verbal harassment aimed at forcing them to beg, and difficulty in terms of being allowed by others to stop begging. It was found that forced child begging was positively associated with living with unknown people, hunger due to food unavailability the previous week, and negatively associated with native beggar children. It was discovered that forced child begging was negatively associated with health-related quality of life and mental health for beggar children. Child begging encompasses elements of coercion and the deprivation of human freedom. These factors collectively amount to instances of forced labor and/or modern slavery. Policies should ensure that beggar children are removed from harm's way, and that those forcing children to beg are brought to justice.
Keywords: J10; J13; J46; J70; I14; 330; beggar children; forced labor; coercion; modern slavery; health-related quality of life; mental health